Analysis of first permanent molar condition on Kindergarten student aged 5-6 years old in Eastern Suburban Area of Makassar City - Marhamah Marhamah; Rafikah Hasyim; Dwi P. Wulansari; Muliaty Yunus; Hendrastuty Handayani; Sumintarti Sumintarti; Sri Ramadhany (DiscoverSys Inc., 2020)
Objective: The aim of this study was to analyze the first permanent molar condition on kindergarten student aged 5-6 years old in eastern suburban area of Makassar city.Material and method: This study was a descriptive observational study on 100 kindergarten students from four schools in Tamalanrea District, Makassar City. Data was collected with clinical examination and interview. Data was gathered in terms of DMFT status of first permanent molar and OHI-S. Data was analyzed with descriptive statistics and t-test. In this descriptive cross-sectional study. Statistical analysis was performed by descriptive statistics and t-test.Results: Mean DMFT of first permanent molars was 1.00 ± 1.10, with a higher value seen among boys. Mean decayed teeth component was 0.95, followed by filled (0.10) and missing (0.0) components. Conclusion: The observed oral hygiene status among the 5-6 year-olds necessitates implementing pre-ventive as well as restorative measures to improve the oral health status of the young population.